Syncope due to Recurrent Asystole in the Recovery Phase of Exercise Testing - Reis, Caio Vittor Roque de Almeida; Maynarde, Israel Guilharde; Balestra, Luciana Fernandes; Gardenghi, Giulliano (JOURNAL OF CARDIAC ARRHYTHMIAS, 2025)
We describe a clinical case of a 20-year-old male who was referred for an exercise stress test, undergoing cardiologic follow-up for 11 years due to episodes of syncope. Shortly after the end of the exercise phase, he presented recurrent episodes of asystole, associated with loss of consciousness, followed by spontaneous recovery.